Duplication of SOX9 associated with 46,XX ovotesticular disorder of sex development - López-Hernández, Berenice; Méndez, Juan Pablo; Coral-Vázquez, Ramón Mauricio; Benítez-Granados, Jesús; Zenteno, Juan Carlos; Villegas-Ruiz, Vanessa; Calzada-León, Raúl; Soderlund, Daniela; Canto, Patricia (Reproductive biomedicine online, 2018)
The purpose of the present study was to investigate whether ten unrelated SRY-negative individuals with this sex differentiation disorder presented a double dose of SOX9 as the cause of their disease. Ten unrelated SRY-negative 46,XX ovotesticular disorder of sexual development (DSD) subjects were molecularly studied. Multiplex-ligation dependent probe amplification (MLPA) and quantitative real-time PCR analysis (qRT-PCR) for SOX9 were performed. The MLPA analysis demonstrated that one patient presented a heterozygous duplication of the entire SOX9 coding region (above 1.3 value of peak ratio), as well as at least a ~ 483 kb upstream duplication. Moreover, no duplication of other SOX9 probes was observed corresponding to the region between −1007 and −1500 kb upstream. A qRT-PCR analysis showed a duplication of at least −581 kb upstream and ~1.63 kb of the coding region that encompasses exon 3. The limits of the duplication were mapped approximately from ~71539762 to 72122741 of Chr17. No molecular abnormalities were found in the remaining nine patients. This study is thought to be the first report regarding a duplication of SOX9 that is associated with the presence of 46,XX ovotesticular DSD, encompassing at least −581 kb upstream, and the almost entire coding region of the gene.